The German workers and the Nazis - Carsten, Francis L., 1911-1998 1911-1998 (Scolar Press, 1995)
Although there have been innumerable monographs and books on the attitude of the German workers to National Socialism, there has been no comprehensive study of the subject. Interest has focused on resistance and opposition, not on the attitude of the large majority who were passive or indifferent, more interested in their working conditions and wages than in political questions; but there was also an active pro-Nazi minority. The active opposition consisted of Communists, Social Democrats and Independent Socialists - another comparatively small minority, the members of which suffered cruel persecution. Partly based on the author's own experience, The German Workers and the Nazis combines an account of the German working-class opposition to Hitler and the Nazis with a description of the workers' daily problems and mood - which ranged from support to total opposition - during the 12 years of the Third Reich.